PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN HONDA BRIO PADA KONSUMEN HONDA SEMARANG CENTER - Gandes Swari Romadhiani; Sudharto Prawoto Hadi (Jurnal Ilmu Administrasi Bisnis, 2017)
The numbers of vehicle competitors in Indonesia make consumers have many alternatives to fulfill their needs. Brand image is a set of beliefs of consumers from a certain brands, while product quality is the entire features and characteristics of a product that are able to satisfy the stated or implied needs of the product. Brand image and product quality plays an important role in influencing purchase decision. This purpose of this study was to determine the effect of variable brand image and product quality on purchase decision Honda Brio on Honda Semarang Center. Type of research is explanatory research with 91 respondents drawn by using accidental sampling technique. The data collection techniques used questionnaires and interviews. The data analyses techniques used regression analysis with SPSS (Statistical Product and Service Solutions) version 20.0. The results of research showed that the brand image has an effect on purchasing decisions with a correlation coefficient of determination coefficient of 0.597 and 35.6%, product quality has an effect on purchasing decisions with a correlation coefficient of 0.646 and a coefficient of determination of 74.1%. Brand image and product quality together have an effect on purchasing decisions by the equation Y = 3,702 + 0,360 X1 + 0,367 X2. This means that the effect of brand image and product quality will improve purchasing decisions.Conclusion of the study is brand image and product quality influence on purchase decisions. Advices for that company based on this research are to strengthen the brand image of product and to evaluate its product quality